The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1980-5373-mr-2015-0482
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Stability and Crystallographic Analysis of the the Sr2HoNbO6 Cubic Perovskite as Potential Substrate for YBa2Cu3O7-δ Superconducting Films

Abstract: The Sr 2 HoNbO 6 complex perovskite has been synthesized by solid-state reaction. X-ray diffraction pattern reveals that Sr 2 HoNbO 6 material crystallizes in a cubic structure, Fm3̅ m space group, lattice constant a=8.018 Å, which has a lattice mismatch ~3% with YBa 2 Cu 3 O 7-δ . The chemical stability of Sr 2 HoNbO 6 with YBa 2 Cu 3 O 7-δ superconducting has been studied by x-ray diffraction and measurements of magnetization as a function of temperature on Sr 2 HoNbO 6 -YBa 2 Cu 3 O 7-δ composites. X-ray di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The investigation of chemical stability for the reduced compositions was performed by XRD measurements and microstructural studies. From the results as reported in Figure 9, it was found that the XRD patterns of the samples SST5, SST10, SST15, and SST20 show similarity with earlier samples, and no signature of structural and chemical degradations was observed [60,61]. Additionally, FESEM images of corresponding reduced compositions (inset in Figure 9) also confirm that the microstructure was not modified by reduction.…”
Section: Electrical Conductivity and Chemical Stabilitysupporting
confidence: 56%
See 1 more Smart Citation
“…The investigation of chemical stability for the reduced compositions was performed by XRD measurements and microstructural studies. From the results as reported in Figure 9, it was found that the XRD patterns of the samples SST5, SST10, SST15, and SST20 show similarity with earlier samples, and no signature of structural and chemical degradations was observed [60,61]. Additionally, FESEM images of corresponding reduced compositions (inset in Figure 9) also confirm that the microstructure was not modified by reduction.…”
Section: Electrical Conductivity and Chemical Stabilitysupporting
confidence: 56%
“…The investigation of chemical stability for the reduced compositions was performed by XRD measurements and microstructural studies. From the results as reported in Figure 9, it was found that the XRD patterns of the samples SST5, SST10, SST15, and SST20 show similarity with earlier samples, and no signature of structural and chemical degradations was observed [60,61]. Therefore, both extrinsic defects, caused by the Sm doping at the Sr-site and intrinsic oxygen vacancies [59], formed under the reducing conditions, subsidize the formation of electrons and the increase of electrical conductivity.…”
Section: Electrical Conductivity and Chemical Stabilitymentioning
confidence: 64%
“…So far, there are very few reports of double perovskites produced through this technique [6][7] . Double perovskites are materials extensively studied due to the potential that their generic formula AA'MM'O 6 , where A-and A'-cation, and M-and M'-cations can be the same or different type, provides to modify the structure and, consequently, the physical properties of this family of compounds, by introducing various elements in sites A and M of that formula [8][9] . The novel double perovskite material LaBiFe 2 O 6 has recently been reported as a possible biferroic with ferromagnetic and ferroelectric response at room temperature 10 .…”
Section: Introductionmentioning
confidence: 99%